2019
DOI: 10.2174/1381612825666190117164901
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Nanoparticle-based Delivery of Next Generation Peptide Nucleic Acids

Abstract: Background: Peptide nucleic acids (PNAs) belong to the next generation of synthetic nucleic acid analogues. Their high binding affinity and specificity towards the target DNA or RNA make them the reagent of choice for gene therapy-based applications. Objective: To review important gene therapy based applications of regular and chemically modified peptide nucleic acids in combination with nanotechnology. Method: Selective research of the literature. Results: Poor intracellular delivery of PNAs has been a sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 74 publications
0
16
0
Order By: Relevance
“…Since their discovery, PNAs have been established as a versatile tool with a wide range of therapeutic and diagnostic applications. Multiple studies have successfully utilized PNAs for targeting mRNAs [6] , non-coding RNAs (microRNAs) [7 , 8 , 9 , 10] and genomic double stranded (ds)DNA [11 , 12 , 13] for regulating gene expression [14 , 15] . In addition to anti-sense and gene editing applications, PNAs have also been used for DNA barcoding [16] , biosensors [17] and as an anti-infective agent [18] .…”
Section: Peptide Nucleic Acids (Pnas)mentioning
confidence: 99%
“…Since their discovery, PNAs have been established as a versatile tool with a wide range of therapeutic and diagnostic applications. Multiple studies have successfully utilized PNAs for targeting mRNAs [6] , non-coding RNAs (microRNAs) [7 , 8 , 9 , 10] and genomic double stranded (ds)DNA [11 , 12 , 13] for regulating gene expression [14 , 15] . In addition to anti-sense and gene editing applications, PNAs have also been used for DNA barcoding [16] , biosensors [17] and as an anti-infective agent [18] .…”
Section: Peptide Nucleic Acids (Pnas)mentioning
confidence: 99%
“…For these reasons, alternative technologies have been explored for PNA delivery, consisting in the non-covalent association of these oligonucleotides with nanoscaled vehicles and nanoparticles [40,41]. The use of nanoparticles and related systems have some advan-tages with respect to the covalent association with small-and macromolecules, including versatility of the loading procedures, increased rates of internalization and release, and ease of modifications for obtaining multifunctional systems.…”
Section: Peptide Conjugationmentioning
confidence: 99%
“…In order to solve this drawback, the various approaches that have been considered (Figure 2) can be differentiated into: (a) cellular delivery, (b) specific delivery in the subcellular compartment, and (c) tissue delivery for in vivo studies. In this review, we will focus on the use of multifunctional and multicomponent delivery systems to enable the cellular uptake of PNAs, with the aim to give a general view on this subject that update what reported in previous reviews [39] or extend more recent works describing only some aspect of nanoparticle-based PNA transport [40,41]. Additionally, the description of the approaches exploiting these types of oligonucleotides as building blocks for multifunc- Being very efficient tools for modulating gene expression both in vitro and in vivo, PNAs and their analogues have been proposed as antisense molecules capable of blocking mRNA or correcting aberrant pre-mRNA splicing (Figure 2a) [21][22][23], a field that has recently boosted research on novel antimicrobial agents [24][25][26], as anti-gene agents, thus blocking transcription from DNA to mRNA (Figure 2b) [27][28][29], as anti-miR agents, blocking this important regulative class of non-coding RNAs (Figure 2c) [30][31][32][33], and as "decoy" molecules capable of sequestering transcription factors (Figure 2d) [34].…”
Section: Introduction 1peptide Nucleic Acids and Their Usesmentioning
confidence: 97%
See 1 more Smart Citation
“…Numerous studies have been reported on FDA approved poly-lactic-co-glycolic-acid (PLGA) polymers for delivery of plasmid DNA [16], siRNA [17] and peptide nucleic acid (PNAs) [1821]. In prior reports it has been found that PLGA nanoparticles (NPs) coated with a cell penetrating peptide can deliver PNAs-based antimiRs in vitro and in vivo [22].…”
Section: Introductionmentioning
confidence: 99%